2016
DOI: 10.14814/phy2.13038
|View full text |Cite
|
Sign up to set email alerts
|

Altered CO2 sensitivity of connexin26 mutant hemichannels in vitro

Abstract: Connexin26 (Cx26) mutations underlie human pathologies ranging from hearing loss to keratitis ichthyosis deafness (KID) syndrome. Cx26 hemichannels are directly gated by CO 2 and contribute to the chemosensory regulation of breathing. The KID syndrome mutation A88V is insensitive to CO 2, and has a dominant negative action on the CO 2 sensitivity of Cx26WT hemichannels, and reduces respiratory drive in humans. We have now examined the effect of further human mutations of Cx26 on its sensitivity to CO 2 . Mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 50 publications
(91 reference statements)
3
30
0
Order By: Relevance
“…The key result from our study is that Cx26 gap junctions are closed by a direct action of CO2 on the protein. Our prior publications have demonstrated the opening action of CO2 on Cx26 hemichannels (Huckstepp et al, 2010a;Meigh et al, 2013;Meigh et al, 2014;de Wolf et al, 2016;de Wolf et al, 2017;Cook et al, 2019;Dospinescu et al, 2019). This paper further shows that these diametrically opposite actions of CO2 on gap junctions and hemichannels depend on the same residues and presumably the same carbamate bridging mechanism.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…The key result from our study is that Cx26 gap junctions are closed by a direct action of CO2 on the protein. Our prior publications have demonstrated the opening action of CO2 on Cx26 hemichannels (Huckstepp et al, 2010a;Meigh et al, 2013;Meigh et al, 2014;de Wolf et al, 2016;de Wolf et al, 2017;Cook et al, 2019;Dospinescu et al, 2019). This paper further shows that these diametrically opposite actions of CO2 on gap junctions and hemichannels depend on the same residues and presumably the same carbamate bridging mechanism.…”
Section: Discussionsupporting
confidence: 68%
“…Thus, the KIDS mutations not only prevent CO2dependent opening of the hemichannel, but also prevent CO2-dependent closing of the gap junction, at least when combined with M151L. Interestingly, the effect of N14K on hemichannel sensitivity to CO2 is less than the other KIDS mutations (de Wolf et al, 2016) and this parallels the trend in our data that permeation of NBDG through the Cx26 N14K,M151L gap junctions, while still occurring, may be slightly slowed at the higher level of PCO2 ( Figure 6C, D).…”
Section: Effect Of Kid Syndrome Mutations On Co2-dependence Of Gap Jumentioning
confidence: 95%
See 1 more Smart Citation
“…Auditory transduction involves high energy consumption in the cochlea and concomitant CO 2 production, and thus CO 2 may evoke Cx26 hemichannel-dependent ATP signaling for coordination of supporting cell activity. At least two DFNB1 mutations interfere with CO 2 -mediated hemichannel opening, which would impair signaling: p.(Met34Thr), which reduces the ability of the hemichannel to open in response to CO 2 , and p.(Ala88Ser; Frei et al, 2002 ), with a reduced affinity for CO 2 (de Wolf et al, 2016 ).…”
Section: Genetic Alterations That Results In Dfnb1 Hearing Impairmentmentioning
confidence: 99%
“…Furthermore, c.101T>C transfected HeLa cells did not transfer Lucifer yellow (a fluorescent dye) to neighbors across gap junctions compared to wild-type connexin 26 transfected cells 20,22,24 and the ability to transfer neurobiotin was also reduced. 21 However, c.101T>C transfected HeLa cells was able to load the dye in response to non-physiological zero extracellular Ca 2+ stimulus 25 , suggesting that the Met34Thr variant connexin may retain some residual function under unusual circumstances. The atomic structure of the human connexin 26 gap junction channel revealed that the methyl group in Met34 in the first transmembrane domain interacts with the tryptophan at amino acid position 3 in the amino-terminal helix of an adjacent protomer to stabilize the hexameric channel 26 , and alteration of the residue is predicted to impact function 27 .…”
Section: Functional Datamentioning
confidence: 99%